2021
DOI: 10.3389/fpsyg.2021.748712
|View full text |Cite
|
Sign up to set email alerts
|

Therapists’ Experiences With the Effectiveness and Feasibility of Videoconference-Based Eye Movement Desensitization and Reprocessing

Abstract: Research on the effectiveness and applicability of eye movement desensitization and reprocessing (EMDR) via videoconference is sparse. Considering the emerging use of internet-based psychotherapy during the COVID-19 pandemic, information on videoconference-based EMDR (eEMDR) would be beneficial for many therapists. In this study, 23 therapists from the EMDR-Institute in Germany provided information about their experiences with eEMDR in a questionnaire-based survey. Information on the effectiveness and the cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Overall, most therapists and clients in our evaluation said that online EMDR was a safe and effective mode of delivering therapy. A questionnaire-based survey which explored therapists’ experiences of online EMDR reported that therapists rated 91% of the online EMDR sessions as ‘good’ or ‘very good’ (Mischler et al, 2021 ). In addition, it was shown that the patient-reported subjective unit of disturbance (SUD) when recalling trauma decreased by more than 70% from the beginning to the end of the online EMDR sessions, which is similar to the SUD decrease reported in the in-person EMDR sessions (Ironson et al, 2002 ; Wilson et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, most therapists and clients in our evaluation said that online EMDR was a safe and effective mode of delivering therapy. A questionnaire-based survey which explored therapists’ experiences of online EMDR reported that therapists rated 91% of the online EMDR sessions as ‘good’ or ‘very good’ (Mischler et al, 2021 ). In addition, it was shown that the patient-reported subjective unit of disturbance (SUD) when recalling trauma decreased by more than 70% from the beginning to the end of the online EMDR sessions, which is similar to the SUD decrease reported in the in-person EMDR sessions (Ironson et al, 2002 ; Wilson et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review investigating the effects of online EMDR ( 28 ) found only one eligible trial showing that combined internet delivered CBT and EMDR successfully reduced self-rated and clinician-rated PTSD from baseline to follow-up ( 29 ). A handful of studies exist on the effectiveness of online EMDR, and findings show clinically meaningful reductions in PTSD, depression, and anxiety ( 30 ) and similar outcomes, based on subjective units of distress (SUDs), compared to previous EMDR studies delivered face-to-face ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is different from computerized treatment, which is delivered without a therapist. 8 Although there is currently only limited research on online EMDR therapy, surveys suggest that psychotherapists are conducting online psychotherapy with their patients, 9 , 10 especially during the COVID-19 pandemic. Eye movement desensitization and reprocessing associations around the world have drawn up guidelines for the practice of online EMDR therapy.…”
mentioning
confidence: 99%